Pendampingan Digital Branding Melalui Reaktivasi Lokasi Google Maps Berstatus Tutup Permanen : Abdimas UD. Pia Toulip Digital Branding Assistance Through Reactivation of Google Maps Locations with Permanently Closed Status : Service to Society UD. Pia Tou - Lorine Tantalu; Sri Handayani; Wildan Eka Prasetya; Sudirman Sudirman (JAST : Jurnal Aplikasi Sains dan Teknologi, 2026)
UD. Pia Toulip is an MSME producing various traditional snacks in Malang Regency that has been operating for over ten decades. Due to the impact of the Covid-19 pandemic, business activities declined, leading to the loss of the owner's digital account credentials and causing the Google Maps profile to automatically change to "Permanently Closed." This unmanaged profile significantly reduced search visibility, hindered promotional reach, and triggered negative perceptions among potential consumers. This Community Service (PKM) program aimed to restore the partner's digital branding existence through strategic interventions, namely digital location reactivation and management access recovery on the Google Business Profile platform. The execution method involved re-claiming the business profile using a new account, system verification, and optimizing the business’s operational data. The results of the program demonstrated the successful reactivation of the account to an active public status. The tangible impact of this restored digital visibility was an acceleration in both upstream and downstream business aspects. The production capacity of the flagship product, milk pie, surged by 200% with oven efficiency reaching 67%. Furthermore, the partner's weekly turnover experienced a fantastic increase of 300%. The market reach also expanded beyond the owner's initial targets, growing from a single city area into four regional areas: Malang Regency, Batu City, Sidoarjo, and Surabaya. In conclusion, restoring digital identity through Google Business Profile has successfully recovered consumer trust and established sustainable economic independence for UD. Pia Toulip.